„It will be so neither” or the role of local management in local development in case of two settlements - Gerencsér, Ilona; Tóth, Tamás (Studia Mundi – Economica, 2017)
The aim of our paper is to highlight the decisive role of local governments in the spatial politics, and in particular of the village leaders. The possibilities for development of settlements in natural and social conditions - geographical location, number of inhabitants, education of people living there, etc. - in addition, the way and thinking of driving thinking is another determining factor. The paper explores a good example of a local economic development research and successful village leaders, trying to show the importance of local actors’ activity.